Successful treatment of donor‐derived hepatitis C viral infection in three transplant recipients from a donor at increased risk for bloodborne pathogens. Issue 2 (22nd February 2017) - Shah, Ashesh P.; Cameron, Andrew; Singh, Pooja; Frank, Adam M.; Fenkel, Jonathan M.
Abstract: We report here the successful treatment of hepatitis C virus (HCV) transmitted from a nucleic acid testing (NAT)‐negative donor to three HCV‐negative recipients—two renal transplants and one liver. Both renal recipients underwent standard deceased‐donor renal transplantation with immediate graft function. The liver recipient underwent standard orthotopic liver transplantation and recovered uneventfully. The donor was a 39‐year‐old woman with a terminal serum creatinine of 0.7 mg/dL. She was high risk for bloodborne pathogens, based upon a history of sexual contact with an HCV‐infected male partner. Recipient 1 was a 45‐year‐old man with a history of end‐stage renal disease from systemic lupus erythematosus. Recipient 2 was a 62‐year‐old woman with a history of end‐stage renal disease caused by hypertension and insulin‐dependent diabetes. Recipient 3 was a 42‐year‐old man with acute liver failure from acetaminophen ingestion. All recipients became HCV polymerase chain reaction positive on post‐transplant follow‐up. Both kidney recipients were treated with ledipasvir/sofosbuvir combination therapy for 12 weeks without side effects or rejection episodes. Recipient 3 was treated with ledipasvir/sofosbuvir in combination with ribavirin for 12 weeks without side effects. All patients achieved a sustained viral response at 12 weeks and are considered cured of HCV. The kidney recipients maintained good allograft function with a serum creatinine of 1.4 mg/dL and 1.0 mg/dL, respectively. Both renal recipients maintained normal liver function post treatment and did not develop any evidence of fibrosis. The liver recipient's liver function tests returned to normal without further incident. This case report provides evidence for the successful treatment of donor‐derived HCV in transplant recipients.